Gifts and Conflicts of Interest: In Shades of Gray? [Presentes E Conflitos de Interesses: Uma Área Cinza?] [Los Regalos Como Conflicto de Interés: ¿Una Zona Gris?] - Pasmanik-Volochinsky, D; Winkler-Muller, M (Organizacion Panamericana de la Salud, 2018)
Gifts are a regular practice within the relationships established by business world stakeholders with the professionals that may be instrumental in promoting their sales. Consequently, gifts are a potential source of conflicts of interest. This article is the result of a bibliographic study of papers addressing gifts, published in scientific journals which was carried out with the aim of identifying what kinds of professions address the issue and in what ways, in order to reach conclusions that may enhance reflection and contribute to professional training. The research was carried out using the SciELO, PsychNet, IEEE, and Proquest databases and yielded 59 publications that span the period between 1998 and 2015. Results show a remarkable concentration in health-related professions, mainly in their relationships with the pharmaceutical industry. Nevertheless, an emerging presence is being observed in other professional fields. Starting from a philosophical conceptualization of the gift as a present, the results suggest that it is not this conception of gift but rather the exchange rationality that is reflected in these practices, thus becoming an ethically gray, i.e., uncertain area, that cannot be disregarded when it comes to training in professional ethics. © 2018, Organizacion Panamericana de la Salud. All rights reserved.